Antibacterial compounds from propolis of Tetragonula laeviceps and Tetrigona melanoleuca (Hymenoptera: Apidae) from Thailand - Sirikarn Sanpa (2018)
© 2015 Sanpa et al. This study investigated the chemical composition and antimicrobial activity of propolis collected from two stingless bee species Tetragonula laeviceps and Tetrigona melanoleuca (Hymenoptera: Apidae). Six xanthones, one triterpene and one lignane were isolated from Tetragonula laeviceps propolis. Triterpenes were the main constituents in T. melanoleuca propolis. The ethanol extract and isolated compounds from T. laeviceps propolis showed a higher antibacterial activity than those of T. melanoleuca propolis as the constituent α-mangostin exhibited the strongest activity. Xanthones were found in propolis for the first time; Garcinia mangostana (Mangosteen) was the most probable plant source. In addition, this is the first report on the chemical composition and bioactivity of propolis from T. melanoleuca.